PENGENALAN DIVERSIFIKASI PENGELOLAAN DAUN KELOR (Moringa oleifera L.) SEBAGAI UPAYA PENCEGAHAN STUNTING PADA ANAK SEKOLAH DASAR DI DESA SOKKOLIA: PENGENALAN DIVERSIFIKASI PENGELOLAAN DAUN KELOR (Moringa oleifera L.) SEBAGAI UPAYA PENCEGAHAN STUNTING PADA ANAK SEKOLAH DASAR DI DESA SOKKOLIA - Asmawati, Andi; Ristiana, Evi; Pratiwi, A. Citra (Jurnal Pengabdian Kepada Masyarakat Patikala, 2023)
Nutritional problems such as stunting are problems that often occur and are a major problem in developing countries. Moringa leaves (Moringa oleifera) are a source of food that has high nutritional value. Due to the diverse content of Moringa leaves, it is very necessary to innovate processed foods that can attract public interest so that Moringa leaves are widely used and become one of the vegetables of choice that can improve the standard of living of local people. This training is carried out by presenting material supported by practices regarding leaf diversification. Moringa. Activities are divided into 3 main stages, namely: material delivery stage, training (production) stage, and evaluation stage. The food innovations made from Moringa leaves include fried rice, Moringa omelettes, Moringa pizza and Moringa pudding. From the organoleptic test, the average results were found to be in the range of interesting and very interesting indicators. with an assessment in terms of color, taste, aroma and acceptability